Resilience and vulnerability of neural speech tracking after hearing restoration - Alessandra Federici; Marta Fantoni; Francesco Pavani; Giacomo Handjaras; Evgenia Bednaya; Alice Martinelli; Martina Berto; Franco Trabalzini; Emiliano Ricciardi; Elena Nava; Eva Orzan; Benedetta Bianchi; et al. (Communications Biology)
Abstract The role of early auditory experience in the development of neural speech tracking remains an open question. To address this issue, we measured neural speech tracking in children with or without functional hearing during their first year of life after their hearing was restored with cochlear implants (CIs), as well as in hearing controls (HC). Neural tracking in children with CIs is unaffected by the absence of perinatal auditory experience. CI users and HC exhibit a similar neural tracking magnitude at short timescales of brain activity. However, neural tracking is delayed in CI users, and its timing depends on the age of hearing restoration. Conversely, at longer timescales, speech tracking is dampened in participants using CIs, thereby accounting for their speech comprehension deficits. These findings highlight the resilience of sensory processing in speech tracking while also demonstrating the vulnerability of higher-level processing to the lack of early auditory experience.